In-vitro α amylase and glycosidase inhibitory effect of ethanolic extract of antiasthmatic drug - Shirishadi - Divya Kajaria; Ranjana; Jyotishankar Tripathi; Yamini Bhushan Tripathi; Srikant Tiwari (Wolters Kluwer Medknow Publications, 2013)
Asthma and diabetes have strong relationship; both are cause and effect of each other. Oxidative stress due to bronchial asthma may cause insulin resistance whereas lack of proper insulin can cause defective smooth muscle relaxant. There is no single medicine available that can manage both diseases, rather the mainstay treatment of bronchial asthma causes hyperglycemia. Keeping this problem in focus, in this study the hypoglycemic effect of an indigenous antiasthmatic Ayurvedic drug Shirishadi was evaluated. Pancreatic alpha amylase and glucosidase inhibitors offer an effective strategy to lower the level of post prandial hyperglycemia via control of starch breakdown. For evaluation of hypoglycemic activity of drug, in-vitro alpha amylase and alpha glucosidase enzyme inhibition was calculated. Ethanolic extract of compound showed 76.40% + 0.88% reduction in alpha amylase activity and 63.85% + 0.36% in alpha glucosidase activity with IC 50 0.68 mg/ml and 2.89 mg/ml, respectively. This study suggests that the ethanolic extract of Shirishadi polyherbal compound effectively acts as alpha amylase and glucosidase inhibitor leading to a reduction in starch hydrolysis and hence acts as antiasthmatic as well as hypoglycemic drug.